TELAAH KAPASITAS PEREMPUAN SEBAGAI PEMIMPIN DI ERA MODERN PERSPEKTIF HADIS - Mufid Abdul; Aziz Tegar Wahana; Muth Mainnah; Deny Marita Wijayanti (Jurnal Keislaman, 2022)
This study aims to find out and further analyze how the capacity of women to become leaders in the modern era using the perspective of hadith. In addition, it also aims to determine the capacity of women to become leaders in the modern era by using hadith as a research reference. Women's leadership is still a matter of unresolved debate. Al-Quran verses and hadiths that help the scholars in terms of leadership are still a complicated idea. Cleric's interpretation often says that even the capacity for opportunity to become a leader has a narrow range of motion. The method used in this research is qualitative with a systematic literature review model. The results of this study indicate that women have the capacity to lead, even though they are not in leadership and must have the ability to lead. In addition, it shows that the hadith used as the basis for prohibiting women from leading does not actually say that women are prohibited from becoming leaders only by the presence of a leader and these things are based on different social circumstances.